Printing apparatus for displaying color information control method and storage medium thereof - LEE, BYUNG HWA (2022)
A printing apparatus of the present invention comprises: a printer part; a display part for displaying a screen; and a setting part configured to set one of a first setting for displaying a screen with standard color information and a second setting for displaying a screen with color information different from standard color information. If the second setting is set, the color information of a screen displayed by the display part is changed. When the screen viewed by the display part includes a code image to be read by an external device, the code image is not displayed with the color information of the code image changed even if the second setting is set. A feature of the present invention is to provide a technique that enables an external device to accurately recognize a coded image even when the printing apparatus displays the screen according to color information different from standard color information. 본 발명의 인쇄장치는, 프린터부와, 화면을 표시하는 표시부와, 표준의 색 정보로 화면을 표시하는 제1 설정과, 표준의 색 정보와는 다른 색 정보로 화면을 표시하는 제2 설정 중 어느 한개를 설정하는 설정부를 구비한다. 제2*정이 설정되어 있는 경우에, 표시부가 표시하는 화면의 색 정보를 변경하고, 표시부가 의시하는 화면에, 외부장치에 의해 판독될 코드 화상이 포함되어 있는 경우, 제2 설정이 설정되어 있어도, 코드 화상을, 코드 화상의 색 정보가 변경된 상태로 표시하지 않도록 한다.